Blade of the Immortal Volume 14: Last Blood - Samura, Hiroaki (Dark Horse, 2019)
Rin has spent countless days chasing the murderer of her parents, and now she has Anotsu Kagehisa where she wants him, but the deathly ill Anotsu is too sick for the honor-bound Rin to strike down. But such is not the case for the students of the Shingyoto-ryu, who are out to avenge the death of their sword master, and they have Rin captured and Anotsu cornered. The spirit of revenge is thick in the air -- and about to get thicker as Manji, Rin's immortal bodyguard, finally reunites with his charge as this pot of retribution prepares to boil over. And so Manji's faced with a strange irony -- to save Rin, he must cut down the men who are out to kill Anotsu, Manji's sworn enemy!